Development of LKPD Based on Contextual Teaching Learning (CTL) on Ecosystem Material to Train Learning Independence - Yulianti, Mika; Nopriyeni, Nopriyeni; Hidayat, Tomi (Universitas Islam Negeri Ar-Raniry, 2026)
The aim of this research is to develop contextual teaching materials to increase students' learning independence and optimize the connection between learning materials and real-life contexts. This study uses a research and development method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of fifth-grade students in the limited and extensive testing stages. Data collection techniques included expert validation sheets, teacher and student response questionnaires, and learning independence observation sheets. Data were analyzed descriptively quantitatively and qualitatively. The results showed that the developed CTL-based LKPD met the criteria of very valid with a validation percentage of media experts of 94% and material experts of 92%. The practicality level in the limited test obtained a percentage of 93%, while in the extensive test it reached an average of 94.5% with a very practical category. The effectiveness of the LKPD is shown by the results of observations of the extensive trial which are in the independent category, with an average score of 15 (Class A) and 14 (Class B), with no students in the less independent category. Based on these results, it can be concluded that the CTL-based LKPD on the ecosystem material developed is declared valid, very practical, and effective in training students' learning independence, so it is suitable for use as teaching materials in science learning in elementary schools. Keyword: Contextual Teaching and Learning; ecosystem; independent learning; research; Student worksheet.